Computational and experimental approaches for development of methotrexate nanosuspensions by bottom-up nanoprecipitation - dos Santos, Aline Martins [UNESP] (2017)
Development of nanosuspensions offers a promising tool for formulations involving poorly water-soluble drugs. In this study, methotrexate (MTX) nanosuspensions were prepared using a bottom-up process based on acid-base neutralization reactions. Computational studies were performed to determine structural and electronic properties for isolated molecules and molecular clusters in order to evaluate the mechanism of MTX nanoparticle formation. Computational results indicated that the clusters in zwitterionic and cationic states presented larger dimensions and higher energies of interaction between MTX molecules, which favored aggregation. In contrast, the clusters in the anionic state exhibited lower energies of interaction, indicating aggregation was less likely to occur. Experimental results indicated that the higher the HCl proportion during drug precipitation, the greater the particle size, resulting in micrometric particles (2874–7308 nm) (cationic and zwitterionic forms). However, MTX nanoparticles ranging in size from 132 to 186 nm were formed using the lowest HCl proportion during drug precipitation (anionic form). In vitro release profiles indicated that the drug release rate from nanosuspension was increased (approximately 2.6 times) over that of the raw material. Overall, computational modeling and experimental analysis were complementary and assisted in the rational design of the nanosuspension based on acid-base reactions.